UPAYA PENINGKATAN KOMPETENSI GURU DALAM PEMBUATAN SKENARIO PEMBELAJARAN INOVATIF MELALUI IHT (IN HOUSE TRAINING) DI SD NEGERI 1 WIROTAMAN - Subekti, Bambang Dwi (Universitas PGRI Adi Buana Surabaya, 2019)
Considering the condition of teachers in Elementary School Wirotaman 1 Ampelgading Malang, which at the moment most of them still use the Learning Implementation Plan copy-paste results, and remember the importance of making innovative learning scenarios in a Learning Implementation Plan, on this occasion researchers intend to improve teacher competency especially in making innovative learning scenarios through In House Training in Elementary School Wirotaman 1 Ampelgading Malang